Improvisasi Gerakan 1821 Sebagai Upaya Revitalisasi Defradasi Karakter dan Kualitas Pendidikan Indonesia Pada Siswa Kelas V SD Negeri Kuluran - Angelina Dea Miranda; Richa Alfina Maulidiyah; Agung Setyawan (MURABBI, 2022)
Character education is one of the most important aspects in an effort to prevent the looser character in Indonesia. Based on the Regent's regulation Number 24 of 2019, the 1821 movement program was launched to support the realization of character education as well as harmony in the family sphere. The type of research used in this study is a qualitative research method with a descriptive approach. The result of this study yhat the 1821 movement gave rise to positive responses, both for student and their enverioment. Online learning methods trigger the degradation of children’s character, it can be seen from the many students who abuse existing facilities, even learning like this causes juvenile delinquency. As an effort to revitalize the degradation of children's character and efforts to improve the quality of education through Focus Group Discussions (FGD).